Philippine cinema, 1897-2020 - Vibal, Gaspar A.; Villegas, Dennis Santos (Artefilipino, 2020)
This lavishly illustrated art book not only provides a dazzling retrospective of over a hundred years of Philippine cinema, it also simultaneously traces its history, genres, narratives, tropes and lore while subjecting its rich filmography to critique and film theory. The book tracks Philippine cinematic beginnings as a technological marvel and its many turns up to the twenty-first century as it blindly accepted, appropriated, indigenized, and even attacked Western conventions through intentionally wicked but hilarious parodies.